Green Synthesis of Silver Nanoparticles Using Lemon Peels for Fabrication of an Electrochemical Sensor for Sulfamethoxazole Detection (Samarra Journal of Pure and Applied Science, 2026)
Sulfamethoxazole (SMX), a widely used sulfonamide antibiotic, plays a critical role in bacterial infection treatment by inhibiting folic acid synthesis. This study presents an electrochemical sensor for SMX detection, incorporating silver nanoparticles (AgNPs) synthesised via green chemistry using lemon peel extract. The synthesised AgNPs were conjugated with SMX to form an ion-pair complex (SMX-AgNPs), which was applied to a graphite rod to create an ion-selective electrode (ISE). Characterisation of the AgNPs and SMX-AgNPs was performed using UV-visible spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive X-ray spectroscopy (EDX). The fabricated electrode exhibited a broad linear detection range from 1×10⁻¹ to 1×10⁻⁷ M, with exceptional stability for 65 days and rapid response times. The sensor demonstrated high sensitivity and selectivity, offering an efficient, eco-friendly, and cost-effective method for SMX quantification in pharmaceutical and environmental applications. This work highlights the potential of AgNPs-based sensors in enhancing drug detection, presenting a reliable and sustainable approach for pharmaceutical analysis.